The use of biomass for electric power generation in the South African and Zimbabwean saw-milling industry - Cochrane, Edward Denzil Dundonald (Energy Research Centre, 2016)
This paper considers the opportunities for the South African and Zimbabwean Saw-milling Industry to be self-sufficient in the generation of power for its own industrial electrical energy requirements. The analysis of the wood residue arising from saw-milling operations in the southern African context confirms that there is a substantial amount of fuel available for the main heating requirement of a wet saw-mill. This heat is generally supplied in the form of steam to the timber drying and conditioning kilns that form part of the timber production process. One of the principal arguments put forward for cogeneration is that by passing steam through a condensing or back pressure turbine the entire power demand of a saw-mill can be met as well as the heat for the kilning process. Due to the situation of unbalanced load that persists at nearly all the saw-mills, there is a surplus of power that is often difficult to dispose of economically.